2021
DOI: 10.1002/aocs.12565
|View full text |Cite
|
Sign up to set email alerts
|

Composition, anti‐inflammatory, and antioxidant activities of avocado oil obtained from Duke and Fuerte cultivars

Abstract: Avocado (Persea americana Mill.) fruit and oil are traditionally used for their antioxidant, anti-inflammatory and anti-aging properties. We investigated chemical variability between two avocado cultivars (Duke and Fuerte) in relation to their antioxidant and anti-inflammatory activities. Duke cultivar showed higher β-carotene and α-tocopherol content but significantly lower lipid content (36% dry weight) compared to Fuerte (52% dry weight). The ethanolic extract of Duke cultivar showed good antioxidant proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The mass temperature was 230 °C and Quad 150 °C. The identification of different constituents was determined by comparing the spectrum fragmentation pattern with those stored in Wiley and NIST Mass Spectral Library data, as described previously [ 39 , 40 ]. The contents of derivatized components were determined based on a percentage of peak areas relative to the summed peak area percent of all identified metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…The mass temperature was 230 °C and Quad 150 °C. The identification of different constituents was determined by comparing the spectrum fragmentation pattern with those stored in Wiley and NIST Mass Spectral Library data, as described previously [ 39 , 40 ]. The contents of derivatized components were determined based on a percentage of peak areas relative to the summed peak area percent of all identified metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…Avocado is rich in nutrients, containing a variety of vitamins, tocopherols, and trace metal elements such as calcium, magnesium, and zinc, and the oil in the avocado pulp mainly consists of various monounsaturated fatty acids and polyunsaturated fatty acids, of which oleic acid accounts for 34% to 81%, 7.2–38.9% for palmitic acid, 6–26.6% for linoleic acid, 2.1–5.8% for linolenic acid, etc. [ 1 , 2 , 3 ]. Avocado oil has been applied to the development of products that aid in lowering blood pressure, are anti-inflammatory, and promote wound healing, with promising applications [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The functionality of avocado oil was closely related to its nutritional composition, while the nutritional quality of avocado oil was influenced by factors such as fruit variety [ 3 , 13 ], extraction method [ 14 ], and fruit storage method [ 15 ]. Lozano et al [ 13 ] confirmed that total sterols were higher in immature fruits (1.1–6.2%) than in mature fruits (0.8–2.0%) in four avocado varieties, “Zutano”, “Bacon”, “Fuerte”, and “Lula”.…”
Section: Introductionmentioning
confidence: 99%